Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{1}{c}=\frac{1}{2}\left(\frac{1}{a}+\frac{1}{b}\right)\)
\(\frac{1}{c}:\frac{1}{2}=\frac{1}{a}+\frac{1}{b}\)
\(\frac{2}{c}=\frac{a+b}{ab}\)
\(\Rightarrow2ab=ac+bc\)
\(\Rightarrow ac-ab=ab-bc\)
\(\Rightarrow a.\left(c-b\right)=b.\left(a-c\right)\)
\(\Rightarrow\frac{a}{b}=\frac{a-c}{c-b}\)( đpcm )
2: \(A=9^n\cdot81-9^n+3^n\cdot9+3^n\)
\(=9^n\cdot80+3^n\cdot10\)
\(=10\left(9^n\cdot8+3^n\right)⋮10\)
4/ \(\left\{{}\begin{matrix}\dfrac{x}{3}=\dfrac{y}{4}\\\dfrac{y}{5}=\dfrac{z}{6}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\dfrac{x}{15}=\dfrac{y}{20}\\\dfrac{y}{20}=\dfrac{z}{24}\end{matrix}\right.\Leftrightarrow\dfrac{x}{15}=\dfrac{y}{20}=\dfrac{z}{24}=k\) (đặt k)
Suy ra \(x=15k;y=20k;z=24k\)
Thay vào,ta có:
\(M=\dfrac{2.15k+3.20k+4.24k}{3.15k+4.20k+5.24k}=\dfrac{186k}{245k}=\dfrac{186}{245}\)
Ta có \(\frac{a+b}{c}=\frac{b+c}{a}=\frac{c+a}{b}=\frac{2(a+b+c)}{a+b+c}=2 \)
=> a+b=c
b+c=a
c+a=b
M=\(\frac{a+b}{b}.\frac{b+c}{c}.\frac{c+a}{a}=\frac{(a+b)(b+c)(c+a)}{abc}=2.2.2=8 \)
ta có : \(\dfrac{a}{c}=\dfrac{c}{b}\Leftrightarrow ab=c^2\)
khi đó ta có : \(\dfrac{b-a}{a}=\dfrac{b^2-a^2}{a^2+c^2}\Leftrightarrow\dfrac{b-a}{a}=\dfrac{\left(b-a\right)\left(b+a\right)}{a^2+ab}\)
\(\Leftrightarrow\dfrac{b-a}{a}=\dfrac{\left(b-a\right)\left(b+a\right)}{a\left(a+b\right)}\Leftrightarrow\dfrac{b-a}{a}=\dfrac{b-a}{a}\) (luôn đúng)
\(\Rightarrow\) (đpcm)
Đặt :
\(\dfrac{a}{b}=\dfrac{c}{d}=k\)
\(\Leftrightarrow\left\{{}\begin{matrix}a=bk\\c=dk\end{matrix}\right.\)
\(VT=\dfrac{a}{a-b}=\dfrac{bk}{bk-b}=\dfrac{bk}{b\left(k-1\right)}=\dfrac{k}{k-1}\left(1\right)\)
\(VP=\dfrac{c}{c-d}=\dfrac{dk}{dk-d}=\dfrac{dk}{d\left(k-1\right)}=\dfrac{k}{k-1}\left(2\right)\)
Từ \(\left(1\right)+\left(2\right)\Leftrightarrowđpcm\)
Câu 2:
Theo đề, ta có: \(\dfrac{10a+b}{a+b}=\dfrac{10b+c}{b+c}\)
=>10ab+10ac+b^2+bc=10ab+10b^2+ac+bc
=>9ac-9b^2=0
=>ac-b^2=0
=>ac=b^2
=>a/b=b/c
Ta có :
\(\dfrac{1}{c}=\dfrac{1}{2}\left(\dfrac{1}{a}+\dfrac{1}{b}\right)\)
\(\Rightarrow\dfrac{1}{a}+\dfrac{1}{b}=\dfrac{1}{c}:\dfrac{1}{2}\)
\(\Rightarrow\dfrac{1}{a}+\dfrac{1}{b}=\dfrac{1}{c}\cdot\dfrac{2}{1}\)
\(\Rightarrow\dfrac{1}{a}+\dfrac{1}{b}=\dfrac{2}{c}\)
\(\Rightarrow\dfrac{b}{ab}+\dfrac{a}{ab}=\dfrac{2}{c}\)
\(\Rightarrow\dfrac{a+b}{ab}=\dfrac{2}{c}\)
\(\Rightarrow2ab=\left(a+b\right)c\)
\(\Rightarrow ab+ab=ac+bc\)
\(\Rightarrow ac-ab=ab-bc\)
\(\Rightarrow a\left(c-b\right)=b\left(a-c\right)\)
\(\Rightarrow\dfrac{a}{b}=\dfrac{a-c}{c-b}\)
Vậy \(\dfrac{a}{b}=\dfrac{a-c}{c-b}\)